Optimizing Islamic Education Knowledge to Enhance Graduate Quality from Madrasah Aliyah - Khairiah Khairiah; Irsal Irsal (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Optimizing Islamic Education Knowledge to Enhance Graduate Quality from Madrasah AliyahObjective: This research aims to analyze the strategy of optimizing Islamic Religious Education knowledge's use to improve the quality of Madrasah Aliyah graduates. This research was conducted in 2024. Methods: The research design used qualitative methods with a descriptive approach. Data collection: research data consists of primary and secondary data sources. Data analysis using the Miles and Huberman model includes data collection, reduction, data reduction, data display, and conclusions. Results: Islamic education science has not been optimally carried out in improving the quality of student graduates, so the quality of student graduates has not improved optimally. Conclusion: The concept of the use of the science of Islamic education, which is not well organized and professional, is the basis for difficulties in improving the quality of graduates. The difficulty in improving the quality of student graduates is due to the lack of understanding of the usefulness of the science of Islamic education, which has not been optimized. Contribution: This research can contribute to developing and evaluating the Islamic education curriculum in Madrasah Aliyah by understanding the aspects that need to be optimized.INDONESIAN: Optimalisasi Pemanfaatan Ilmu Pendidikan Agama Islam untuk Meningkatkan Kualitas Lulusan Madrasah AliyahTujuan: Penelitian ini bertujuan untuk menganalisis strategi optimalisasi pemanfaatan ilmu Pendidikan Agama Islam dalam meningkatkan kualitas lulusan Madrasah Aliyah. Penelitian ini dilaksanakan pada tahun 2024. Metode: Desain penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Pengumpulan data: data penelitian terdiri dari sumber data primer dan skunder. Analisis data menggunakan model Miles dan Humberman mencakup pengumpulan data, reduksi data, reduksi data, tampilan data, dan kesimpulan. Hasil: kegunaan ilmu pendidikan Islam belum optimal dilakukan dalam meningkatkan mutu lulusan siswa, sehingga mutu lulusan siswa belum meningkat secara optimal. Kesimpulan: Konsep kegunaan ilmu penddikan Islam yang yang tidak terorganisir dengan baik dan profesional menjadi dasar kesulitan meningkatkan mutu lulusan. Kesulitan meningkatkan mutu lulusan siswa disebabkan pemahaman kegunaan ilmu pendidikan Islam yang belum optimal dilakukan. Kontribusi: Penelitian ini dapat memberikan kontribusi dalam pengembangan dan evaluasi kurikulum pendidikan Islam di Madrasah Aliyah dengan memahami aspek-aspek yang perlu dioptimalkan.